Follow-up on long-term antiretroviral therapy for cats infected with feline immunodeficiency virus. Issue 4 (April 2016) - de Oliveira Medeiros, Sheila; Abreu, Celina Monteiro; Delvecchio, Rodrigo; Ribeiro, Anísia Praxedes; Vasconcelos, Zilton; de Moraes Brindeiro, Rodrigo; Tanuri, Amilcar
Objectives: Feline immunodeficiency virus (FIV) is a lentivirus that induces AIDS-like disease in cats. Some of the antiretroviral drugs available to treat patients with HIV type 1 are used to treat FIV-infected cats; however, antiretroviral therapy (ART) is not used in cats as a long-term treatment. In this study, the effects of long-term ART were evaluated in domestic cats treated initially with the nucleoside transcriptase reverse inhibitor (NTRI) zidovudine (AZT) over a period ranging from 5–6 years, followed by a regimen of the NTRI lamivudine (3TC) plus AZT over 3 years. Methods: Viral load, sequencing of pol (reverse transcriptase [RT]) region and CD4:CD8 lymphocyte ratio were evaluated during and after treatment. Untreated cats were evaluated as a control group. Results: CD4:CD8 ratios were lower, and uncharacterized resistance mutations were found in the RT region in the group of treated cats. A slight increase in viral load was observed in some cats after discontinuing treatment. Conclusions and relevance: The data strongly suggest that treated cats were resistant to therapy, and uncharacterized resistance mutations in the RT gene of FIV were selected for by AZT. Few studies have been conducted to evaluate the effect of long-term antiretroviral therapy in cats. To date, resistance mutations have not been described in vivo.